Half-life measurement of 65Ga with γ-spectroscopy. (June 2019) - Gyürky, Gy; Halász, Z.; Kiss, G.G.; Szücs, T.; Fülöp, Zs
Abstract: The literature half-life value of 65 Ga is based on only one experiment carried out more than 60 years ago and it has a relatively large uncertainty. In the present work this half-life is determined based on the counting of the γ -rays following the β -decay of 65 Ga. Our new recommended half-life is t1/2 = (15.133 ± 0.028) min which is in agreement with the literature value but almost one order of magnitude more precise. Highlights: Based on gamma-spectroscopy the half-life of 65Ga is measured. Systematic uncertainties are carefully studied. The obtained result is (15.133 +- 0.028)min. This results is in agreement with the only available value in literature, but almost one order of magnitude more precise.